Perlindungan Hukum bagi Kreditur atas Gagal Bayar pada Perjanjian Pinjaman Modal Proyek Perumahan: Studi Kasus Putusan Nomor 69/Pdt.G/2025/PN.Jkt.Sel - Risa Dewi Oktaviani; Alitha Dzakiah Albar; Safina Alia Rameyza; Dwi Desi Yayi Tarina (Media Hukum Indonesia (MHI), 2026)
Investment in the property sector, particularly in housing projects, is characterized by high capital requirements and significant risks of default. This research aims to analyze the forms of legal protection available to creditors as the aggrieved party in capital loan agreements and to examine the judicial considerations in Decision Number 69/Pdt.G/2025/PN.Jkt.Sel regarding the fulfillment of creditors' rights. The research methodology employed is normative juridical, using a statutory approach and a case approach. Data sources were derived from secondary data, encompassing primary legal materials such as legislation and court decisions, as well as secondary legal materials, including legal literature. The results indicate that legal protection for creditors is categorized into two forms: preventive protection through the drafting of rigorous contractual clauses and the binding of collateral, and repressive protection through breach of contract (wanprestasi) lawsuits to demand compensation or the execution of collateral. In Decision Number 69/Pdt.G/2025/PN.Jkt.Sel, the court affirmed that the debtor’s failure to adhere to the payment schedule in the housing project constitutes a breach of contract, granting the creditor the right to recover the principal capital along with interest and penalties as agreed.